Tailoring Physicochemical Properties of Iloperidone by Cocrystallization: Design and Characterization of Novel Cocrystals of Iloperidone and 4- amino Benzoic Acid - Rani, Earle R.; Radha, Gadela Venkata (Drug Delivery Letters, 2023)
Background: The current study explores the enhancement of solubility and dissolution rate of a poorly water-soluble drug Iloperidone (IPD) by synthesizing co-crystals (CC) using 4- amino benzoic acid (ABA) as a coformer. Methods: Pharmaceutical CCs of IPD with ABA were designed and synthesized using crystal engineering. CCs were prepared by solvent evaporation (SE) technique and studied for their enhancement in solubility and dissolution rate. CC formation was confirmed by Fourier Transform Infra- Red Spectroscopy (FTIR), powder X-ray diffraction (PXRD), Differential Scanning Calorimetry (DSC), and Proton Nuclear Magnetic Resonance (1H- NMR). Results: Structural characterization studies exhibited new characteristic peaks, which confirmed that CCs could be generated from IPD and ABA using SE technique. The apparent aqueous solubility studies of the CCs exhibited 7.1 folds increase in solubility compared to the pure drug. Improvement in the rate of dissolution of CCs was evident from the in vitro dissolution studies, where CCs displayed 94.15 ± 0.27% drug release in 60min while pure drug showed only 39.90 ± 1.86% release in the same time period. Conclusion: CCs of IPD and ABA provide a novel approach to overcoming the solubility issues.
Keywords: dissolution